2023
DOI: 10.3390/plants12020334
|View full text |Cite
|
Sign up to set email alerts
|

6-Benzyladenine Treatment Maintains Storage Quality of Chinese Flowering Cabbage by Inhibiting Chlorophyll Degradation and Enhancing Antioxidant Capacity

Abstract: The cytokinin 6-benzyladenine (6-BA) is widely used to regulate the growth of horticultural crops. However, it is not clear how postharvest treatment with 6-BA at various concentrations affects the quality of Chinese flowering cabbage. In this study, harvested Chinese flowering cabbage was foliar sprayed with 6-BA solution at concentrations of 5, 10, 20, 40, and 80 mg·L−1. All 6-BA treatments protected the quality of Chinese flowering cabbage during storage, and the treatment with 20 and 40 mg·L−1 6-BA showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The same finding has been shown for blueberries treated with burdock fructooligosaccharides and cherry tomatoes treated with melatonin [ 22 , 23 ]. However, further evidence has also demonstrated that excessive ROS can adversely affect disease resistance [ 24 , 25 , 26 ]. Fruits and vegetables have a self-regulatory protection mechanism that activates the antioxidant defense system, thereby inhibiting excessive ROS accumulation and reducing oxidative damage [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same finding has been shown for blueberries treated with burdock fructooligosaccharides and cherry tomatoes treated with melatonin [ 22 , 23 ]. However, further evidence has also demonstrated that excessive ROS can adversely affect disease resistance [ 24 , 25 , 26 ]. Fruits and vegetables have a self-regulatory protection mechanism that activates the antioxidant defense system, thereby inhibiting excessive ROS accumulation and reducing oxidative damage [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…An additional mechanism employed by antitranspirants involves the inhibition of stomata opening, consequently reducing the water loss from the leaf (Sow and Ranjan, 2021). Growth regulators are recommended to prolong postharvest longevity, benzyl adenine (BA) is one of the growth regulators that delays leaf yellowing and consequently increases leaf longevity (Zhang et al, 2023). Spraying of 6-benzylaminopurine (BAP) at concentrations of 37.5-300 mg L -1 improved postharvest durability of Anthurium andreanum 'Apalai' flower without inducing spathe blueing (Favero et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This sexual modification of flowers suggests that genes responsible for sexual differentiation undergo suppression or activation through a signal transduction mechanism that modifies endogenous hormone levels, as observed in Jatropha curcas [ 29 , 30 ]. Studies have shown that 6-benzyladenine can also inhibit lipid peroxidation, preserve membrane integrity in plant tissues [ 31 ] increase antioxidant capacity, and delay leaf senescence in Brassica campestris species [ 32 ].…”
Section: Introductionmentioning
confidence: 99%